2018
DOI: 10.18178/ijtef.2018.9.5.618
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Knowledge Taxpayer, Moral Taypayer and Tax Sanctions on Taxpayers Compulsory

Abstract: This research examine the relationship between knowledge taxpayer, moral taxpayer, tax sanctions, taxpayers Compulsory. Objects in this study are Taxpayer Knowledge, Taxpayer Moral, Tax Sanctions, and Taxpayer Compliance. This research was conducted at KPP Pratama Bandung. Therefore the authors use population data from taxpayers who are active in reporting taxes even though it may not be in every year. Sample determination technique used in this research is non probability sampling. Sampling is done by distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
2
12
0
12
Order By: Relevance
“…Sanksi diperlukan untuk memberikan pelajaran bagi para pelanggar pajak. Dengan demikian, diharapkan peraturan pajak dipatuhi oleh wajib pajak (Purnamasari & Sudaryo, 2018).…”
unclassified
“…Sanksi diperlukan untuk memberikan pelajaran bagi para pelanggar pajak. Dengan demikian, diharapkan peraturan pajak dipatuhi oleh wajib pajak (Purnamasari & Sudaryo, 2018).…”
unclassified
“…In addition, an increase in sanctions in causing a deterrent effect can be realized if the losses suffered due to the imposition of sanctions are much more significant than the potential gains (Dularif, 2019). The results of previous studies found that tax sanctions affect taxpayer compliance (Purnamasari & Sudaryo, 2018;Widuri &Wati, 2019 andPuspitasari, 2019). Different results were found by Oladipupo & Obazee (2015) and Meidawati & Azmi (2019) which stated that tax sanctions did not affect taxpayer compliance.…”
Section: Introductionmentioning
confidence: 94%
“…Taxpayers who have good morals as citizens in carrying out their tax obligations are different from citizens who do not have moral awareness. The results of previous studies found that taxpayer morale affected taxpayer compliance (Purnamasari & Sudaryo, 2018;Tusubira & Nkote, 2013;Cahyonowati, 2011). Different results were found (Salman, Sutrisno & Komarudin, 2008) and Mustikasari (2007), which stated that taxpayer morale did not affect taxpayer compliance.…”
Section: Introductionmentioning
confidence: 95%
“…General affairs related to the duties of the State which organizes the government. Tax is compulsory contribution from the person, to the government to debt the expenses incurred in the common interest of all, without reference to special benefits conferred (Purnamasari & Sudaryo, 2018). Tax is a mandatory contribution from the person, to the government to pay the costs incurred for the benefit of the person common of all, without reference to conperred specific benefits.…”
Section: Taxmentioning
confidence: 99%